(untitled) (Acta Entomologica Serbica, 2019)
Three new true bugs were recorded in Serbia and species are listed with notes on records. Anisops sardeus Herrich-Schäffer, 1849; Henestaris laticeps (Curtis, 1836); Caenocoris nerii (Germar, 1847).